Protection of reproductive health of children: problems of gender and age discrimination - M.M. Blikhar; І.М. Zharovska; І.І. Komarnytska; Р.М. Matkivska; Y.V. Mervinska (Publishing House TRILIST, 2023)
Research objectives: to investigate the problems of gender and age discrimination in the modern discourse on the protection of children's reproductive health, to analyze the most important issues including the concept of child reproductive health, normative guarantees in the field of children's reproductive health, protection of reproductive children's health in the context of achieving the Sustainable Development Goals of the United Nations, social obstacles to the proper realization of children's reproductive rights, etc. Materials and methods. A survey was based on the author's developed questionnaires in order to find out the level of reproductive health and sexual violence among children. The focus group was formed by 540 children: 288 girls and 252 boys aged 15-18 living in Lviv, Ivano-Frankivsk and Zakarpattia regions. The research period covered the years 2021-2023. The error of the obtained results, taking into account the number of respondents, was 2-3.5%. The questionnaires are designed for anonymous and quick filling. Results. Today's problems and challenges of an environmental, pandemic, and military nature are partially offset by rapid and continuous improvements in social and economic conditions, along with changes in demographics, lifestyles, the environment, and innovations in medical and therapeutic technologies. In general, there is sufficient number of normative protection guarantees that exist at the normative level. However, the problem is manifested in the fact that declarative norms are often ineffective, as they do not entail real guarantees of an organizational and institutional nature regarding the protection and protection of children's medical rights. Despite the special needs and vulnerabilities that children face, most services are not organized to recognize or meet these needs. Conclusions. It is substantiated that the family is the most important institution in the socialization of a child, and its life experience plays an important role in ensuring that the child is a healthy individual in the broad sense of this concept, which includes physical and psychological criteria. It has been established that characteristics and relationships in the family, especially in the preschool period (the most critical process of children's development) can positively or negatively affect the structure of the child's personality. Sudden changes and extraordinary events experienced by the family in the process of adaptation to social changes can cause the family to experience a crisis situation.